Geographies of production and the contexts of politics: dis-location and new ecologies of fear in the Veneto città diffusa - Bialasiewicz, L. (Environment and Planning D: Society and Space, 2025)
Scholars of regionalist mobilisation have focused their attentions largely on the ideal and idealised landscapes that are an integral part of regional mythmaking, noting the ways in which such ‘representative landscapes’ are deployed by regional ideologues to convey belonging and emplace identity. I argue that to understand regionalist mobilisation it is equally important to consider the lived, everyday spaces of the region, spaces within which such regionalist politics are born. In this paper, I focus on the Veneto region in the Italian North East: one of the wealthiest productive areas in Europe but also the site of some of the most reactionary regionalist and localist rhetorics. I explore the links between the transformations in the Veneto’s production landscapes over the past decades and the emergence of new political discourses, arguing that it is only through an understanding of the new geographies of production and consumption that structure the Veneto space—a space that is increasingly deterritorialised and decentred, suspended between its rural past and an unaccomplished urbanisation—that we can begin to understand fully the region’s increasingly exclusionary identity politics, and the ways in which the globalised Veneto città diffusa that has made its fortunes on the global market and on global migrants is increasingly reacting against both and finding refuge in hyperlocalised myths of belonging.
EPrint Processing Status: Author unable to supply full text
Keywords: Regionalist mobilisation; North-east Italy; Production; Consumption; Local politics; Identity.